2018
DOI: 10.4049/jimmunol.1701086
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt Signaling in CD11c+ APCs Regulates Microbiota-Induced Inflammation and Immune Cell Homeostasis in the Colon

Abstract: Aberrant Wnt/β-catenin signaling occurs in several inflammatory diseases, including inflammatory bowel disease and inflammatory bowel disease-associated colon carcinogenesis. However, its role in shaping mucosal immune responses to commensals in the gut remains unknown. In this study, we investigated the importance of canonical Wnt signaling in CD11c APCs in controlling intestinal inflammation. Using a mouse model of ulcerative colitis, we demonstrated that canonical Wnt signaling in intestinal CD11c APCs cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 58 publications
(126 reference statements)
0
43
0
Order By: Relevance
“…Wnt/β-catenin signaling was recorded with anti-in ammatory effects in the development of ulcer colitis [35]. As previous studies described, with the activating of canonical Wnt signaling, β-catenin would accumulate in cytoplasm and regulates the expressions of Wnt-related genes [65].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Wnt/β-catenin signaling was recorded with anti-in ammatory effects in the development of ulcer colitis [35]. As previous studies described, with the activating of canonical Wnt signaling, β-catenin would accumulate in cytoplasm and regulates the expressions of Wnt-related genes [65].…”
Section: Discussionmentioning
confidence: 97%
“…Proved by previous reports, Wnt/β-catenin pathway is involved in regulating cell differentiation, embryonic development, tissue regeneration and other important physiological processes [32,33]. However in recent years, accumulating researches have revealed its another important role which was associated with the immunoregulatory porperties in various immune-related in ammations and auto-immune diseases, comprising cancer, rheumatoid arthritis, enteritis and so on [34][35][36]. Wnt/β-catenin pathway is partcipating in regulating the development and differentiation of immunocytes [30] and exhibiting encouraging and promising anti-in ammatory effects in chronic disease, such as in ammatory bowel disease [37][38][39].…”
mentioning
confidence: 99%
“…In animal models of colon carcinogenesis, the use of nonsteroidal anti-inflammatory drugs (NSAIDs) can inhibit antigen-presenting cells and control intestinal inflammation and intestinal immune homeostasis via the canonical signal Wnt [100]. In fact, commensal-polarized macrophages induce gene mutation, chromosomal instability, and endogenous transformation through microbiome-induced bystander effects (MIBE) that activate Wnt/β-catenin signaling [101].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…4C). It has been shown that the expression of Wnt ligands was increased in several colitis mouse models (18,19), and also that the Wnt−β-catenin signaling is pivotal for homeostasis of the intestinal epithelium by promoting stem cell renewal (20). In keeping with these data, the expression of WNT ligands, WNT2, WNT2B, and WNT4, was drastically increased in colon samples treated with DSS, whereas it was significantly decreased upon a treatment with either Dex, CpdX, CpdX(eA), CpdX(eB), CpdX-D3, CpdX-D3(eA), or CpdX-D3(eB) (Fig.…”
Section: Significancementioning
confidence: 99%